ECOTOXICOLOGICAL RISK POTENTIAL DUE TO HYDROCARBONS IN THE COASTALMARINE ECOSYSTEM OF VENTANILLA, CALLAO-PERU: PART - I - Argota Pérez, George (2022)
The purpose of the study was to describe the ecotoxicological potential for hydrocarbons in the coastalmarine ecosystem of Ventanilla, Callao-Peru. It is mentioned that petroleum hydrocarbons, when adsorbed on particulate materials, sediments, and the tissues of aquatic fauna, cause an ecological imbalance. Likewise, liver damage and gills of fish are produced, affecting growth and productivity in biomass. The effects can be acute (eg mortality, necrosis, mutagenicity, suffocation) and chronic (egbiomagnification processes and loss of biodiversity). A conservative type ecotoxicological risk predictionwas made using the Gecotoxic® computer program where the environmental analysis descriptorindicated a high type rating (81%), while the environmental effect descriptor was also high prediction, but at 100%. It is concluded that various parameters must be evaluated to consider the risks to human health,such as equivalent potency concentration, matrix sweep value, lifetime carcinogenic risk model, maximum daily consumption, and toxic equivalency factors. In the same way, it must understand several questions in the dynamics of reversibility for the affected areas and among which are mentioned: 1st) what invertebrate organisms can be considered as future indicators of coastal-marine environmental quality, 2nd) how will the fauna evolve? macrobenthic? 3rd) in what time will the trophic interaction be restored? 4th) which threatened or endangered species were affected? and 5th) how much is the economic impact on traditional fishing communities?